The Effect of Wadiah Savings and Problem Financing (NPF) in the 'Precise Sharia Financing' Product on the Profitability Level of PT. Bank BTPN Syariah Tbk for the Period 2015 - 2023 - Dewi, Aulia Siska Puspita; Moch Khoirul Anwar; Maryam Bte Badrul Munir (Perisai : Islamic Banking and Finance Journal, 2024)
This study aims to empirically examine the effect of wadi'ah savings and non-performing financing (NPF) on profitability (ROA) in the Precise Syariah Financing product at PT Bank BTPN Syariah during the period 2015 - 2023. Using an associative quantitative approach. The study conducted by researchers using secondary data derived from BTPN Syariah quarterly financial statements for the period 2015 - 2023. The data analysis technique used multiple linear regression analysis through Eviews 12 as a data processing tool. The study results showed that an increase in wadi'ah savings significantly positively contributed to an increase in ROA, while an increase in NPF had a significant negative effect. The regression model developed was able to explain 71.15% of ROA variability. This finding explains that an increase in wadi'ah savings tends to increase profitability, while an increase in NPF tends to decrease the level of profitability of BTPN Syariah. The implication is that banking management needs to focus on managing the increase in wadi'ah savings and improving the quality of financing to increase profitability. This study provides important insights for Islamic banking management in optimizing financial performance, especially in the context of the Tepat Pembiayaan Syariah product and contributes to the literature on factors affecting the profitability of Islamic banks in Indonesia. This study contributes to the Islamic banking literature, but has limitations in terms of the research period and variables used. Future research is expected to expand the scope of variables and periods in the study to obtain generalized results.